2017
DOI: 10.1007/s40121-017-0175-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of Opportunities to Improve Antibiotic Prescribing in an Emergency Department: A Period Prevalence Survey

Abstract: IntroductionApproximately 30% of all outpatient antimicrobials are inappropriately prescribed. Currently, antimicrobial prescribing patterns in emergency departments (ED) are not well described. Determining inappropriate antimicrobial prescribing patterns and opportunities for interventions by antimicrobial stewardship programs (ASP) are needed.MethodsA retrospective chart review was performed among a random sample of non-admitted, adult patients who received an antimicrobial prescription in the ED from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 40 publications
3
25
0
1
Order By: Relevance
“…The patterns of antimicrobial prescribing in veterinary emergency and critical care (ECC) settings have not been previously described. A study of human emergency room (ER) practice found that 39% of antimicrobial drug prescriptions were inappropriate (21). This observation raises questions regarding the appropriateness of prescribing in veterinary ECC settings.…”
Section: Introductionmentioning
confidence: 99%
“…The patterns of antimicrobial prescribing in veterinary emergency and critical care (ECC) settings have not been previously described. A study of human emergency room (ER) practice found that 39% of antimicrobial drug prescriptions were inappropriate (21). This observation raises questions regarding the appropriateness of prescribing in veterinary ECC settings.…”
Section: Introductionmentioning
confidence: 99%
“…Beta‐lactams are the most commonly used first‐line antibiotics globally, with cephalosporin use approaching penicillin use in recent decades . It was previously reported that a cross‐reactive cephalosporin allergy occurs in 10% of penicillin‐allergic patients .…”
Section: Introductionmentioning
confidence: 99%
“…Beta-lactams are the most commonly used first-line antibiotics globally, with cephalosporin use approaching penicillin use in recent decades. [1][2][3] It was previously reported that a cross-reactive cephalosporin allergy occurs in 10% of penicillin-allergic patients. 4 This figure relates to studies prior to the 1980s, which demonstrated cross-reactivity between benzylpenicillin and first and second generation cephalosporins.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are still needed to evaluate the benefit of stewardship initiatives for acute bacterial skin and skin structure infections (ABSSSI), bloodstream infections, central nervous system infections, and intra-abdominal infections. Timbrook et al concluded that inappropriate antibiotic prescribing was observed in 39% of ED cases in their study [35]. The disease states that had the highest rates observed included bronchitis, upper respiratory tract infections, and skin and soft-tissue infections, and therefore special attention should be given to improving prescribing patterns for these disease states.…”
Section: Discussionmentioning
confidence: 90%